Debating Khirbet Qeiyafa - Garfinkel, Yosef, 1956- (Jerusalem)
269 s.
Keywords: "In 2007 the name "Khirbet Qeiyafa" was still unknown both to professional archaeologists and to the public. In 2008 Khirbet Qeiyafa became world-famous. This spectacular success is entirely due to the figure of King David, who is so well known from the biblical tradition but is a very elusive figure from the archaeological or historical point of view. Nowhere else had an archaeological layer that can be related to this king been uncovered, not even in Jerusalem. For the first time in the archaeology of Judah, a fortified city from the time of King David had been exposed. The date of the site was obtained by accurate radiometric measurements conducted on short-lived samples of burned olive pits. The location in the Elah Valley, just one day's walk from Jerusalem, places the site in the core area of the Kingdom of Judah. Moreover, it is exactly in this area and this era that the biblical tradition places the famous combat between the inexperienced and anonymous young shepherd David and the well-equipped giant Philistine warrior Goliath. Khirbet Qeiyafa has become the point of contact between archaeology, biblical studies, ancient history and mythology. The fieldwork at Khirbet Qeiyafa lasted seven seasons, from 2007 to 2013. This book, written at the end of the excavation phase, summarizes the main results, supplies answers to various issues concerning the site that have been raised over the last few years, and presents a comprehensive interim report. The authors use this opportunity to discuss various methodological issues that relate to archaeology and the biblical tradition, and how to combine the two." --